Functional and anatomical alterations in bilateral vestibulopathy: A multimodal neuroimaging study and clinical correlation - Lee, Eek-Sung; Weon, Young Cheol; Kim, Ji-Soo; Lee, Tae-Kyeong; Park, Ji-Yun (Frontiers in Neurology, 2023)
Object To investigate alterations in functional and structural connectivity, and brain morphology in patients with bilateral vestibulopathy (BVP) and to determine whether these changes correlate with the severity of dizziness, daily activities, and anxiety level. Methods We compared the findings of resting-state functional MRI (rsfMRI) and diffusion tensor imaging (DTI), and voxel-wise regional brain volume between 13 patients with BVP (7 women; mean age±SD = 63.5±14.7 years, 22 80 years) and 18 age- and gender-matched controls. Additionally, we correlated the neuroimaging parameters with the Dizziness Handicap Inventory score (DHI), Vestibular Disorders Activities of Daily Living Scale (VADL), and Hospital Anxiety and Depression Scale (HADS). Results Compared with controls, BVP patients showed a decreased functional connectivity among the key nodes of the salience network, auditory (including vestibular) network, bilateral posterior parahippocampal gyri, bilateral paracingulate gyri, and right frontoparietal network, and the anatomical connectivity in the right cerebellum, corpus callosum tapetum, and left fornix. The gray matter volume was decreased in the bilateral parahippocampal gyri, right precentral gyrus, anterior cingulate gyrus, and right middle temporal gyrus, and increased in the right superior frontal gyrus in patients with BVP compared to the controls. The anatomical connectivity in the clinically meaningful white matter regions decreased as the scores of DHI and VADL increased. Conclusions This study confirmed the previous findings of diminished hippocampus volume and altered vestibular functional connectivity in BVP and additionally suggested dysfunction of the salience network as a common mediator of cognitive dysfunction due to peripheral sensory loss.